Random lasing in an organic light‐emitting crystal and its interplay with vertical cavity feedback. Issue 5 (15th May 2014) - Camposeo, Andrea; Polo, Marco; Del Carro, Pompilio; Silvestri, Leonardo; Tavazzi, Silvia; Pisignano, Dario
<x xml:space="preserve">Abstract</x> The interplay between vertical‐cavity and random lasing emission properties of a blue‐emitting molecular crystal is investigated. The emission spectra of the 1, 1, 4, 4‐tetraphenyl‐1, 3‐butadiene samples show narrow peaks for excitation threshold >500 μJ cm−2, attributed to both the built‐in vertical Fabry‐Pérot cavity and random lasing. These results pave the way for the realization of solid‐state lasers exploiting various amplification routes based on organic crystals. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>